Effect of Early-Intervention Acupuncture on Pain Relief Among Emergency Department Patients with Suspected Acute Renal Colic Due to Urinary Calculi: Study Protocol for a Randomized Clinical Trial [Letter] - Yang S; Yang W; Gao H (Journal of Pain Research)
Siyue Yang,1,* Wenwen Yang,1,* Hong Gao2 1The Third Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou City, Zhejiang Province, People’s Republic of China; 2Department of Acupuncture and Moxibustion, The Third Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hong Gao, Email qtgh@vip.qq.com